Editorial Preface on the Proceedings of the International Conference and Expo on Magnesium, iMagCon2016. (2017) - Sreekanth, D.; Narayanan, R.; Kottada, Ravi Sankar
Abstract: International Conference and Expo on Magnesium (iMagCon2016), first-of-its-kind international conference in India, dealing solely with magnesium and its alloys, was held during 4 th to 6 th February 2016. It was jointly organized by IIM Chennai Chapter and VIT University. This conference was focused on basic academic research related to magnesium, as well as connected industry challenges. Accordingly, papers presented in the conference are included in this proceeding. Two plenary lectures outlining the evolution of magnesium technology development and the state of the art in research on magnesium were delivered by Prof. Karl U Kainer, Magnesium Innovation Center, Helmholtz – Zentrum Geesthact, Germany, and Prof. Ravi Ravindran, Ryerson University, Canada. Besides, nine keynote lectures on various aspects of magnesium production, processing and characterization were delivered by internationally renowned experts. In addition to the invited lectures, about 40 contributed papers were presented spreading over eight sessions. These papers dealt with practically all aspects of magnesium technology: extraction, casting, thermo-mechanical processing, mechanical behaviour, joining, biomaterial applications, etc. Based on these presentations, 16 manuscripts were communicated by respective authors for possible inclusion in the proceedings. Among them 11 papers were finally shortlisted for inclusion in the final proceedings after going through thorough peer reviewing process. We hope that these papers will immensely benefit the research community working in the area of magnesium alloys.